THE SYSTEM OF SECONDARY PERIODICITIES AND RESONANCES BASED ON LYRAE MAGNETIC FIELD - Skulsky, M. Yu. (Одеські астрономічні публікації, 2017)
Original integral interconsistent and interconnected magnetohydrodynamical system of periodicities and resonances over their long-time variabilities is developed. The study is based upon three different observed secondary periods in Lyrae system and taking into account geometrical features of the nonstandard magnetic field in a losing star, as well as due to the asynchronizm of the orbital and rotational periods.